La naturaleza de los aplicativos de movilidad - de la Rosa Carrillo, Mayra Alejandra (2021)
Ride-hailing apps are a recent phenomenon in Peru that have caused a revolution in the legal conception of the relationship between consumer and provider. The author analyzes the competent authority’s rulings regarding their nature, so that their positioning inside the legal system can be discovered.